MYSTERIOUS EPIRUS: COUNTRY OF SANCTUARIES AND ORACLES - S. Kazarov (Гуманитарные и юридические исследования)
The article is devoted to the sanctuaries and oracles of ancient Epirus, a region located in the north of Greece and considered the most mysterious in the country. Epirus itself was the farthest northern point of ancient Greek civilization. According to the author, the remoteness of Epirus from the cultural centers of Greece led to the lack of knowledge of the Greeks about this region and even to the accusation of epirots of barbarism. The very topography of the region was remarkable for its amazing diversity, including high mountain ranges, marshy lagoons, impassable gorges, high-altitude plateaus, turbulent mountain rivers. It was here that numerous shrines, oracles and other sacred sites arose, the most famous of which is the oracle of Zeus in Dodona. The author for the first time in historiography raised the question of the relationship of the natural conditions of the region with the emergence of various religious places - sanctuaries, oracles, temples, etc. The Dodon oracle, the sanctuary of Zeus in Passaron, the oracle of the dead on Acheron, Nymphae-um in Apollonia, the sanctuary of Asclepius in Buthrotum etc., were widely known not only in the region itself, but in the whole of ancient Greece. However, the most famous of them was the Dodonean oracle, which for a long time was the only thread connecting Epirus with all the rest of Greece. Despite the inaccessibility, pilgrims from all over Greece sought to Epirus. The sacred oak, a magical spring spouting out of the ground, sacred pigeons living on an oak tree, copper cauldrons - they all served as means of divination by which the supreme god Zeus spoke to those who asked him his will. All the sanctuaries here still require further research.